A Thousand Splendid Suns - Khaled Hosseini (Great Britain Bloomsbury Publishing, 2018)
A Thousand Splendid Suns is a breathtaking story set against the volatile events of Afghanistan's last thirty years - from the Soviet invasion to the reign of the Taliban to post-Taliban rebuilding - that puts the violence, fear, hope, and faith of this country in intimate, human terms. It is a tale of two generations of characters brought jarringly together by the tragic sweep of war, where personal lives - the struggle to survive, raise a family, find happiness - are inextricable from the history playing out around them. Propelled by the same storytelling instinct that made The Kite Runner a beloved classic, A Thousand Splendid Suns is at once a remarkable chronicle of three decades of Afghan history and a deeply moving account of family and friendship. It is a striking, heart-wrenching novel of an unforgiving time, an unlikely friendship, and an indestructible love - a stunning accomplishment.
Keywords: Contemporary; Fiction; War; Adult Fiction; Historical fiction